2003
DOI: 10.1038/nbt841
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow–derived stem cells initiate pancreatic regeneration

Abstract: We show that transplantation of adult bone marrow-derived cells expressing c-kit reduces hyperglycemia in mice with streptozotocin-induced pancreatic damage. Although quantitative analysis of the pancreas revealed a low frequency of donor insulin-positive cells, these cells were not present at the onset of blood glucose reduction. Instead, the majority of transplanted cells were localized to ductal and islet structures, and their presence was accompanied by a proliferation of recipient pancreatic cells that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
456
6
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 567 publications
(486 citation statements)
references
References 35 publications
14
456
6
10
Order By: Relevance
“…Unlike MSC, MAPC can be cultured indefinitely in a relatively nutrient-poor medium. MAPC exhibit many of the features and capabilities of embryonic stem cells [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Multipotent Adult Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike MSC, MAPC can be cultured indefinitely in a relatively nutrient-poor medium. MAPC exhibit many of the features and capabilities of embryonic stem cells [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Multipotent Adult Progenitor Cellsmentioning
confidence: 99%
“…In patients in whom autologous bone marrow cells were injected directly into the damaged myocardium, some improvement in cardiac function was documented based on medication use, quality of life and MRI studies [17]. In a separate study, after autologous AC 133+ bone marrow cells were injected into infarction borders following coronary artery bypass grafting (CABG), improved perfusion and cardiac function may have occurred [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Demonstration Of Bone Marrow Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…As evidence of the potential for these cells to treat T1D, bone marrow transplantation has been shown to prevent autoimmune insulitis and diabetes in NOD mice [32]. In addition, recent research in immunodeficient mice with chemically-induced pancreatic damage has shown that bone marrow-derived stem cells may have the capacity to initiate beta cell regeneration [33]. However the mechanism involved in pancreatic regeneration may be somewhat contrary to the classic concept of direct stem cell differentiation into cells of the desired target tissue.…”
Section: Why Stem Cell Therapy In Type 1 Diabetes?mentioning
confidence: 99%
“…However the mechanism involved in pancreatic regeneration may be somewhat contrary to the classic concept of direct stem cell differentiation into cells of the desired target tissue. In their chemically induced diabetes model, Hess et al determined that transplanted bone marrow derived stem cells travel preferentially to damaged organs and initiate tissue regeneration via the organ's own stem cell population [33]. As such, it may be that the role of stem cells in ameliorating T1D is to protect remaining beta cells from further destruction or stimulate remaining tissue to regenerate rather than participating directly in the production of de-novo stem cell derived islets.…”
Section: Why Stem Cell Therapy In Type 1 Diabetes?mentioning
confidence: 99%